Hourly automatic weather station data collected on Zachariae Isstrøm, Northeast-Greenland (2016-2020) and at a Firn Aquifer site, East Greenland (2014-2017) - Maurice Van Tiggelen; Paul C J P Smeets; Carleen H Tijm-Reijmer; Clement Miège; Richard R Forster; Shfaqat Abbas Khan; Eric Rignot; Michiel R van den Broeke (PANGAEA, 2024)
Hourly automatic weather station (AWS) data collected at two sites on the Zachariae Isstrøm between 2016 an 2020 (S22, S23), and at a Firn Aquifer site West from Helheim glacier between 2014 and 2017 (S21). S23 was installed at approx. 145 m a.s.l and 13km from the Zachariae Isstrøm glacier front, and S22 was installed at 535 m a.s.l and 35km from the Zachariae Isstrøm glacier front. S21 was installed at 1660m elevation and c.a. 50km from the Helheim glacier front. The data contains air temperature, humidity, wind speed/direction corrected at standard heights of 2 m and 10 m, all four radiation components, atmospheric pressure, snow accumulation by a sonic ranger, ice ablation by a draw wire (S23 only), and glacier surface velocity (GPS).